Catalytic oxidative chemical treatment for the removal of elemental mercury on carbon steel (SAE 1429) surfac [electronic resource] - Farah Ilyana Khairuddin, 1987- (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012